Redução da proteína bruta e suplementação de l-pidolato de cálcio na ração de poedeiras leves em idade avançada - Santos, Rithiele Dantas dos (2022)
Among the problems related to egg quality, shell quality is the main one reported for eggs intended for consumption. Shell quality tends to decrease with advancing age of laying hens, but this change can be minimized by adopting management and nutrition measures. Thus, this research aimed to evaluate the effects of reducing crude protein in the feed and supplementing with calcium L-Pidolate in laying diet for laying hens at advanced age. It was used 360 lightweight White Layers – Lohmann, aged 78 weeks, distributed in 9 diet treatments, with five repetitions and eight birds per experimental unit. The treatments were designed according to an experimental design entirely randomized, in a factorial scheme 3 x 3 (3 levels of crude protein x 3 levels of calcium L-pidolate), where: 1- normal CP feed without added L-calcium pidolate (control); 2- ration with 5% reduction of CP and without added L-calcium pidolate; 3- feed with 10% reduction of CP and without added L-calcium pidolate; 4- normal CP ration with 150g/ton of L-calcium pidolate ration; 5- CP ration with 5% reduction and added 150g/ton of L-calcium pidolate; 6 - CP fraction with 10% reduction and addition of 150g/ton of L-calcium pidolate ration; 7 - regular CP fraction with 300g/ton of L-calcium pidolate ration; 8 - CP fraction with 5% reduction and addition of 300g/ton of L-calcium pidolate ration; 9 - CP fraction with 10% reduction and addition of 300g/ton of L-calcium pidolate ration. The experimental period was 147 days, divided into 7 periods of 21 days each. There was no significant interaction between the factors studied on the variables of performance, egg quality and economic viability. A 10% reduction in CP (16.04% to 14.43% BW) promoted lower bird performance, but did not influence egg quality and economic viability, whereas calcium L-pidolate supplementation had no effect on any of the variables studied.